2003
DOI: 10.1080/0014013031000121977
|View full text |Cite
|
Sign up to set email alerts
|

Sitting comfort and discomfort and the relationships with objective measures

Abstract: The concepts of comfort and discomfort in sitting are under debate. There is no widely accepted definition, although it is beyond dispute that comfort and discomfort are feelings or emotions that are subjective in nature. Yet, beside several subjective methodologies, several objective methods (e.g. posture analysis, pressure measurements, electromyography (EMG) are in use to assess sitting comfort or discomfort. In the current paper a theoretical framework is presented, in which comfort and discomfort were def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
257
0
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 509 publications
(308 citation statements)
references
References 29 publications
(44 reference statements)
3
257
0
16
Order By: Relevance
“…Feelings of discomfort among wheelchair users can have serious consequences, including equipment abandonment, decreased satisfaction, and an inability to function throughout the day [12]. Previous studies have shown that high peak pressures at the body-seat interface correlated with seating discomfort [13][14]. Qualitative research has also been undertaken with respect to seating and comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Feelings of discomfort among wheelchair users can have serious consequences, including equipment abandonment, decreased satisfaction, and an inability to function throughout the day [12]. Previous studies have shown that high peak pressures at the body-seat interface correlated with seating discomfort [13][14]. Qualitative research has also been undertaken with respect to seating and comfort.…”
Section: Introductionmentioning
confidence: 99%
“…This may be in the form of discomfort eliciting movement or subconscious postural shifts or fidgeting. Many studies over the years have monitored movements in chairs a s metrics of co mfort and function [25][26][27][28], thereby establishing a base of knowledge about sitting as a dynamic activity. Many people at risk of dev eloping PUs are either unable to effectively reposition themselves or are not provided with the sensory feedback that elicits movements.…”
Section: Interventions For Reducing Duration Of Loadingmentioning
confidence: 99%
“…The effect of vibration is quantified by perceived discomfort. Recent studies [2][3] have shown an intricate and complex relation between feelings of discomfort and comfort. In this study, discomfort is used throughout in relation to the perception of vibration.…”
Section: Introductionmentioning
confidence: 99%